2018
DOI: 10.15408/ijee.v4i1.4744
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prior Knowledge on Students’ Listening and Reading Comprehension

Abstract: The research aims to investigate the influence of prior knowledge on students’ listening and reading comprehension at the tenth year of MAN 1 Pekanbaru. This study is a correlational research that involved 75 respondents as a sample from 150 students of the the tenth year of Science classes as the total population. The respondents were selected by using a simple random sampling technique. 20 items of multiple choice of listening test and 20 items of multiple choice of reading test and 15 items of the prior kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…From his study, he noted that the more background knowledge students have about a topic or a subject matter, the more they can easily talk about them. Hasan, Gushendra and Yonantha (2017) found a strong positive correlation between prior knowledge and students' listening comprehension. They concluded that the influence of prior knowledge on students' listening comprehension is very high.…”
Section: Literature Reviewmentioning
confidence: 82%
“…From his study, he noted that the more background knowledge students have about a topic or a subject matter, the more they can easily talk about them. Hasan, Gushendra and Yonantha (2017) found a strong positive correlation between prior knowledge and students' listening comprehension. They concluded that the influence of prior knowledge on students' listening comprehension is very high.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Achieving this highest level also shows that students are able to make a comparison table to answer the problem. It is following the opinion of Schulman that students build an understanding of their initial knowledge [15]. New knowledge relates to the things that already known to students by applying initial knowledge with new experiences and ideas [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is following the opinion of Schulman that students build an understanding of their initial knowledge [15]. New knowledge relates to the things that already known to students by applying initial knowledge with new experiences and ideas [15]. According to Brow, preliminary knowledge is arranged in a scheme where initial mental representations obtained from old experiences help students understand new things [15].…”
Section: Discussionmentioning
confidence: 99%
“…It can build the reader-text relationship, which leads the readers to get closer to the text. Hasan, Gushendra, and Yonantha (2017) propose that by having relevant background knowledge, ELF learners can better comprehend the text they read since it enables them to correlate their knowledge to the texts" content and context. Jannah and Fitriani (2017) conveyed that 50% of students tend to use their background knowledge as a good strategy in answering the Reading Comprehension section of TOEFL.…”
Section: -171mentioning
confidence: 99%